A review on association between menopausal symptoms and cardiovascular risk factors - Kar, Debasmita; Roy, Subho (Anthropological Review, 2024)
Menopausal transition and post-menopausal periods can have short-term and long- term effects on mid-life health of women. The short-term effects include the possibility of experiencing of menopausal symptoms, while the long-term effects include cardiovascular diseases (CVD) risk. The occurrence of menopausal symptoms varies widely within and between populations. Studies indicate that the frequency and severity of menopausal symptoms are linked to CVD risk factors, but the existing literature is divergent and somewhat limited. Thus, women belonging to different populations are likely to be at a different risk of CVD, but the exact physiological mechanism behind this relationship remains unclear. The present narrative review aimed to synthesize the available evidence of menopausal symptoms in association with various conventional CVD risk factors such as blood pressure, total cholesterol and blood glucose levels and obesity, as well as to determine the potential link between these two processes. We undertook a rigorous data base search to identify, examine, and critically assess the existing literature on the associations between menopausal symptoms and CVD risk factors. We applied inclusion and exclusion criteria to filter the retrieved articles and classified the literature into eight major categories. The risk of CVD is higher among women who experience vasomotor, psychological, and urogenital symptoms compared to those who do not experience these symptoms. Our review indicates that menopausal symptoms can be used as markers in assessing CVD risk factors during midlife. Thus there is a need for larger-scale research to support these findings and identify the potential mediators that are controlling this association.